Living conditions of children with intellectual disabilities in Encarnación (UNIHumanitas, 2024)
International organizations such as the World Health Organization (WHO), the United Nations Children's Fund (UNICEF), Teletón; as well as National Institutions, the National Secretariat for Persons with Disabilities (SENADIS) and the Secretariat of Social Action, defined conceptually and operationally the terms "persons with disabilities", "types of disabilities", "quality of life", and concepts related to living conditions and the comprehensive protection of their fundamental rights (WB; WHO, 2011). In this research, which was proposed to know the living conditions of children with intellectual disabilities attending a Special Education Center in the city of Encarnación, through the adoption of a test of quality of life with international standard and from a look at the Paraguayan legislation on the rights approach of each of them; the guidelines made by the Committees are taken as a reference: Committee for the Rights of the Child about the situation of Children with Disabilities in the Republic of Paraguay who "is concerned that there is no general policy or national plan specifically aimed at this sector of the population" (Committee on the Rights of the Child. Session No. 1457, 2010), and the Committee on the Rights of Persons with Disabilities, which recommends the urgent implementation of effective measures for the identification, prevention and protection, particularly of women and girls with intellectual disabilities" (SENADIS, 2014).
Keywords: childhood; intellectual disability; quality of life; human rights